Occurrence of Campylobacter fetus subsp. venerealis and Tritrichomonas foetus dna in bulls from Alagoas State, Brazil - Glaucia Grazielle Nascimento (Semina: Ciências Agrárias, 2018)
The aim of the present study is to diagnose the occurrence of infections caused by Campylobacter fetus subsp. venerealis and Tritrichomonas foetus in reproducer bulls from Alagoas State breeders, Brazil. The total of 162 preputial smegma samples were collected from nelore bulls from ten rural properties in the East, Agreste and Sertão mesoregions. The samples were subjected to the Polymerase Chain Reaction (PCR) technique in order to assess C. fetus subsp. venerealis and Tritrichomonas foetus DNA and cultivated in Modified Diamond Medium (DMM) for Tritrichomonas foetus isolation. Four point nine percent (4.9% - 8/162) of the evaluated bulls were infected with C. fetus subsp. venerealis and 3.0% (5/162) of the sample were infected with T. foetus, which was not isolated in any of the assessed animals. Based on our results, there was C. fetus subsp. venerealis and T. foetus DNA in bulls from Alagoas State, Brazil. Accordingly, it is necessary performing laboratory examinations in animals living in properties breeding animals for reproduction purpose in order to monitor and control such infections.